Entwicklung eines lichtbasierten Fahrerassistenzsystems - Budanow, Marina (Spektrum der Lichttechnik, 2020)
In this work describes the development of a light-based driver assistance system through projections on the road. Under realistic conditions it is shown that information can be transmitted to the driver at night by using projections in front of the vehicle: test persons drive more safely through narrow spaces and react earlier to obstacles. A prototype suitable for road use demonstrates the possibility of a near-series implementation of such a headlamp projection system.